2014
DOI: 10.1063/1.4897635
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of localized surface plasmon resonance in heterostructure copper sulfide nanocrystals

Abstract: Localized surface plasmon resonance (LSPR) in semiconductor nanocrystals is a relatively new field of investigation that promises greater tunability of plasmonic properties compared to metal nanoparticles. A novel process by which the LSPR in semiconductor nanocrystals can be altered is through heterostructure formation arising from solution-based cation exchange. Herein, we describe the development of an analytical model of LSPR in heterostructure copper sulfide-zinc sulfide nanocrystals synthesized via a cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…We implemented a core–shell approach within the framework of the Mie–Gans theory describing oblate particles (see the Supporting Information for details). 48 The core dielectric function of CuS was obtained by fitting the extinction spectrum of the parent CuS nanodisk sample ( d = 19.5 nm, and h = 5.5 nm) with the Drude model and by extracting the Drude parameters (see Figure S13). The estimated high-frequency dielectric constant (ε ∞ = 8.4), the plasmon frequency (ω p = 5.3 eV), and the damping constant (γ = 0.3 eV) are in close agreement with previous works on covellite CuS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We implemented a core–shell approach within the framework of the Mie–Gans theory describing oblate particles (see the Supporting Information for details). 48 The core dielectric function of CuS was obtained by fitting the extinction spectrum of the parent CuS nanodisk sample ( d = 19.5 nm, and h = 5.5 nm) with the Drude model and by extracting the Drude parameters (see Figure S13). The estimated high-frequency dielectric constant (ε ∞ = 8.4), the plasmon frequency (ω p = 5.3 eV), and the damping constant (γ = 0.3 eV) are in close agreement with previous works on covellite CuS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[29][30][31] Partial cation exchange has also been employed to convert Cu 2Àx S NCs to alloys or heterostructures. [21,[32][33][34][35] In addition to cation exchange, epitaxial seeded growth or catalytic SLS-likeg rowth can occur,u sually leading to an augmentation of as econdary phase. [12,14,17,19,20,22,23,36] SLS growth occurs due to the supersaturationo ft he catalysts, leading to the precipitation of as econd phase in a1 Dm anner with the diameter determined by the catalysts ize.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, cation exchange has become a common strategy for converting well‐established Cd‐based II–VI semiconductor NCs of various shapes to Zn‐based equivalents, with Cu 2− x S acting as the intermediate, often with the original anion lattice framework and thus the morphology of the NCs intact . Partial cation exchange has also been employed to convert Cu 2− x S NCs to alloys or heterostructures . In addition to cation exchange, epitaxial seeded growth or catalytic SLS‐like growth can occur, usually leading to an augmentation of a secondary phase .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently developed an analytical model in an attempt to replicate the LSPR shifts for these heterostructures. 53 In this study, we demonstrated the synthesis of dualinterface, heterostructured NCs through cation exchange. The heterostructure consists of a copper sulfide layer capped with zinc sulfide grains in spherical NCs and can be tuned by controlling the extent of the cation exchange reaction.…”
Section: Nano Lettersmentioning
confidence: 99%